GOVERNMENT SUPPORT AND RENEWABLE-ENERGY INVESTMENT IN KAZAKHSTAN - Honshu, Yue; Yermekova, Zhanna; Kurmanbekova, Zhuldyz (Farabi Journal of Social Sciences, 2025)
Purpose. To evaluate how Kazakhstan’s renewable-energy (RE) support policies have influenced private-sector investment and to identify persisting barriers that could prevent the country from reaching its 2030 and 2050 green-transition targets. Design/methodology/approach. A qualitative content-analysis was performed on thirty-eight Kazakh RE laws, decrees and strategic programmes issued between 2009 and 2024. These primary sources were triangulated with fifteen multilateral assessments (ADB, EBRD, IEA, IRENA, UNDP) and twenty-two peer-reviewed studies. Manual thematic coding (Bowen, 2009; Braun & Clarke, 2006) generated six analytical themes: policy stability, financial incentives, regulatory efficiency, investor trust, grid integration and international cooperation. Findings. Feed-in tariffs (FITs) and competitive auctions have effectively decreased price volatility, bringing down the average solar and wind strike prices by approximately 40%.However, three structural bottlenecks—intermittent tariff revisions, high domestic borrowing costs and grid congestion in the resource-rich south—continue to depress investor confidence. Originality. This is the first English-language study to synthesise the full 2009-2024 Kazakh policy corpus and systematically map perceived investment barriers to specific legal instruments in a post-Soviet context. Key words: renewable energy, policy support, investment climate, Kazakhstan, qualitative analysis.